1978
DOI: 10.1007/bf01011724
|View full text |Cite
|
Sign up to set email alerts
|

Percolation and cluster distribution. II. layers, variable-range interactions, and exciton cluster model

Abstract: Monte Carlo simulations for the site percolation problem are presented for lattices up to 64 x 106 sites. We investigate for the square lattice the variablerange percolation problem, where distinct trends with bond-length are found for the critical concentrations and for the critical exponents/~ and 7. We also investigate the layer problem for stacks of square lattices added to approach a simple cubic lattice, yielding critical concentrations as a functional of layer number as well as the correlation length ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…50.0; not shown) permits estimation of the minimum ionic surficial mass below which no electric signals were detected: 50.0 lg cm -2 . It is worth noting that the ionic surficial loading for the 10 filters that did not show any signal, is not far off the theoretical value (24.2 lg cm ) estimated by Weschler (1991) for pure 520 nm NH 4 HSO 4 particles on the basis of the percolation theory (Hoschen and Kopelman 1976;Hoschen et al 1978). However, as Tencer (2008) reported, the value at which the aerosol starts to conduct the electrical signal and at which a bridging process commences, may vary according to the geographical region and the related aerosol properties (chemistry and size).…”
Section: Conductivity Measurements In the Aec: Minimum Aerosol Loadingmentioning
confidence: 99%
“…50.0; not shown) permits estimation of the minimum ionic surficial mass below which no electric signals were detected: 50.0 lg cm -2 . It is worth noting that the ionic surficial loading for the 10 filters that did not show any signal, is not far off the theoretical value (24.2 lg cm ) estimated by Weschler (1991) for pure 520 nm NH 4 HSO 4 particles on the basis of the percolation theory (Hoschen and Kopelman 1976;Hoschen et al 1978). However, as Tencer (2008) reported, the value at which the aerosol starts to conduct the electrical signal and at which a bridging process commences, may vary according to the geographical region and the related aerosol properties (chemistry and size).…”
Section: Conductivity Measurements In the Aec: Minimum Aerosol Loadingmentioning
confidence: 99%
“…It can be shown that the value of p c is proportionally inverse to the size of the "basic element" of the texture (Hoshen et al [9], and also Sec. 2.3 in Pikaz and Averbuch [1] in the context of digital images).…”
Section: On the Relation Between The Co-occurrences Matrices And Connmentioning
confidence: 96%
“…We then go through the velocity matrix and create the velocity cluster map by setting every element of V (x, y) above C · V to 1 and the rest to 0. We then go trough this cluster map and identify the cluster size distribution using a Hoshen-Kopelman algorithm [Hoshen et al (1978)]. By doing this, we can identify the cluster size distribution p(s, C), where s is the size of any given cluster.…”
Section: Velocity Burst Definitionmentioning
confidence: 99%